Case Report: Severe Aortic Valve Regurgitation and Pseudoaneurysm in Aortic Valve-Sparing Operation: The Usefulness of Multimodality Imaging in a Complex Clinical Scenario - Varotto, Leonardo; Spigolon, Luca; Dotto, Alberto; Siviero, Valentina; Scodro, Marta; Cabianca, Ester; Magagna, Paolo; Caprioglio, Francesco (Frontiers in Cardiovascular Medicine, 2021)
Background: Failure of the native aortic valve and degenerative anatomy of ascending aorta in patients with previous Tirone-David operation may represent a clinical challenge, because sometimes the risk of reoperation is prohibitive. Case: We described the case of a patient suffering from severe aortic valve regurgitation and pseudoaneurysm of the aortic arch, 6 years after cardiac surgery operation. The aim of this clinical case was to assess if the complex anatomy of aortic pseudoaneurysm and aortic root geometry can be accurately reproduced from contrast-enhanced computed tomography scan into a three-dimensional (3D) printed model. Based on this procedural method, with the aid of transesophageal 3D ultrasound, we efficaciously treated the patient percutaneously with a combination of transcatheter occluder device plus microcoil embolization and transfemoral aortic valve implantation. The patient was free from complications and the need to redo cardiac surgery. Conclusion: To the best of our knowledge, this is the first description of two simultaneous complications and their staged treatment in a patient with previous aortic valve-sparing operation. This is a useful report in a single 3D model applying such specific technology to these two simultaneous clinical settings.